Influence of the PDMS substrate stiffness on the adhesion of Acanthamoeba castellanii - Gutekunst, Sören B.; Grabosch, Carsten; Kovalev, Alexander; Gorb, Stanislav N.; Selhuber-Unkel, Christine (Beilstein Journal of Nanotechnology, 2014)
Background: Mechanosensing of cells, particularly the cellular response to substrates with different elastic properties, has been discovered in recent years, but almost exclusively in mammalian cells. Much less attention has been paid to mechanosensing in other cell systems, such as in eukaryotic human pathogens.Results: We report here on the influence of substrate stiffness on the adhesion of the human pathogen Acanthamoebae castellanii (A. castellanii). By comparing the cell adhesion area of A. castellanii trophozoites on polydimethylsiloxane (PDMS) substrates with different Young’s moduli (4 kPa, 29 kPa, and 128 kPa), we find significant differences in cell adhesion area as a function of substrate stiffness. In particular, the cell adhesion area of A. castellanii increases with a decreasing Young’s modulus of the substrate.Conclusion: The dependence of A. castellanii adhesion on the elastic properties of the substrate is the first study suggesting a mechanosensory effect for a eukaryotic human pathogen. Interestingly, the main targets of A. castellanii infections in the human body are the eye and the brain, i.e., very soft environments. Thus, our study provides first hints towards the relevance of mechanical aspects for the pathogenicity of eukaryotic parasites.
Keywords: acanthamoeba; cell adhesion; elastic substrates; mechanosensing; silicones